Conformational studies of glycosylated cyclic oligomers of furanoid sugar amino acids. Issue 37 (15th September 2016) - Singh, Nishant; Kandiyal, Pancham Singh; Shukla, Praveen Kumar; Ampapathi, Ravi Sankar; Chakraborty, Tushar Kanti
Abstract: Glycosylation of molecules improve their pharmacological and pharmacokinetic properties. In the current manuscript, we have explored the effect of glycosylation on the structure and function of conformationally well-defined small ring homooligomers derived from a structurally diverse library of sugar amino acids (SAA). Conformational analyses carried out by NMR suggested that these cyclic dimers and trimers have well-defined structures in solution. MD simulations performed based on the restraints obtained from NMR revealed that C2H and CO are positioned outside the plane of the ring and NHs are pointed inside the ring. It was encouraging to note that while the cyclic non-glycosylated homooligomers did not show any antimicrobial activity at all, their glycosylated counterparts showed relatively better activity. The modular design developed here is amenable to further improvement and can serve as a tool to investigate many molecular recognition processes. Graphical abstract: